2015
DOI: 10.1038/pr.2015.223
|View full text |Cite
|
Sign up to set email alerts
|

Plasma MASP-1 concentration and its relationship to recovery from coronary artery lesion in children with Kawasaki disease

Abstract: Background: This study investigated prognostic factors for early recovery of coronary artery lesion (CAL) in children with Kawasaki disease (KD). Methods: Patients hospitalized for KD were enrolled less than 2 wk from the onset of illness and divided into two groups: KD with CAL and KD without CAL. The CAL group was further divided into two subgroups according to the degree of CAL: mild (n = 31) and moderate/severe (n = 6) and further divided into two subgroups according to the age: younger than 1 y (n = 9) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…CD59, a complement regulatory protein, maintains the integrity of blood vessels by protecting endothelial cells from injury in local inflammatory sites. However, CD59 levels in plasma were found to be low at the early stage of KD (Song et al, 2016). In agreement with our results, plasma CD59 concentrations increased in acutephase KD patients compared with subacute-phase KD patients (Zou et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…CD59, a complement regulatory protein, maintains the integrity of blood vessels by protecting endothelial cells from injury in local inflammatory sites. However, CD59 levels in plasma were found to be low at the early stage of KD (Song et al, 2016). In agreement with our results, plasma CD59 concentrations increased in acutephase KD patients compared with subacute-phase KD patients (Zou et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…A dual role for MBL has been proposed in Kawasaki disease depending on the age of the patient, with a pathogenic role favoring disease progression and endothelial damage in older children ( 20 ). Additionally, plasma MASP-1 concentration at the onset of the illness was predictive of the length of recovery time for coronary artery lesions ( 22 ). There is evidence that activation of MASP-1 in the early stage of Kawasaki disease provokes a local vascular inflammatory reaction, resulting in the consumption of MASP-1 ( 22 ).…”
Section: Links Between Mis-c and Kawasaki Disease With The Complementmentioning
confidence: 99%
“…Additionally, plasma MASP-1 concentration at the onset of the illness was predictive of the length of recovery time for coronary artery lesions ( 22 ). There is evidence that activation of MASP-1 in the early stage of Kawasaki disease provokes a local vascular inflammatory reaction, resulting in the consumption of MASP-1 ( 22 ). Another lectin pathway component, ficolin-1, demonstrates reduced serum levels after successful intravenous immunoglobulin (IVIG) treatment in Kawasaki patients ( 23 ).…”
Section: Links Between Mis-c and Kawasaki Disease With The Complementmentioning
confidence: 99%
“…According to these data, plasma levels of MASP-1 are much greater in MI patients than in healthy control individuals, although they are not related to immediate outcomes as determined by the salvage index and nal infarct 34 . Rui-Xia Song 35 found that plasma MASP-1 levels were high in children with Kawasaki disease who were recovering from coronary artery lesions. The above studies support that MASP-1 is linked with coronary artery disease and MI.…”
Section: Discussionmentioning
confidence: 99%